Practical Materials on Private Law of the European Union in Disruptive Environments (VUCA, BANI, GAI) - Pérez Milla, José Javier (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The text analyzes the transformative role of artificial intelligence (AI) in university-level legal education, particularly in the field of Private International Law. Using the VUCA and BANI frameworks, it identifies the cognitive and non-cognitive competencies needed to train legal professionals capable of operating in volatile and uncertain environments. A post-AI pedagogy is proposed, focused on developing critical, contextual, and strategic thinking, with AI serving as a catalyst for active learning. From this perspective, a methodological proposal is presented, consisting of 11 practical exercises designed to integrate GAI into realistic scenarios and enhance complex legal competencies.
Keywords: Artificial intelligence; legal higher education; Private International Law; complex competencies; digital literacy; critical thinking; adaptive learning; VUCA/BANI scenarios